From authonomous monitoring to virtual collaborative research: partnership with the indigenous movement from the Northeast region during covid-19 pandemic as support for social control - Pimentel, Spensy Kmitta; Gomes, Alexandre Oliveira; Pavelic, Nathalie Le Bouler; Andrade, Lara Erendira Almeida de; Julião, Cristiane Gomes; Lima, Paulidayane Cavalcanti de; Santos, Rutian do Rosário; Gomes, Thayná Donato (Saúde e Sociedade, 2023)
In the first months of the covid-19 pandemic, in 2020, indigenous movements and organizations in the Northeast region of Brazil established an extensive network of support and partnerships with groups of researchers and civil society entities to organize campaigns of solidarity with the indigenous peoples. The production of general information and empirical data on how the disease reached indigenous territories and populations constituted one of the main strategies for action. This mobilization was the basis for establishing collaborative networks that investigated how the indigenous peoples faced the pandemic, from an anthropological bias and applying methods that we could define as virtual collaborative research. The article, thus, discusses the potential of this type of partnership for reflection on the Indigenous Health Care Subsystem, arguing that this model can constitute a kind of support for social control exercised by the communities.